Homeopathic Treatment Prevents Surgery in a Case of Pronounced Acute Compartment Syndrome - M, Frass; B, Negedly-Blauensteiner; P, Weiermayer; P, Fibert (Archives of Clinical and Medical Case Reports, 2019)
Acute compartment syndrome (ACS) is a severe disease requiring immediate medical intervention consisting of decompressive surgical fasciotomy and antimicrobial treatment, occasionally leading to amputation of the affected limb. In this case, a patient with ACS is described. The patient received conventional treatment for pronounced acute compartment syndrome consisting of relevant medicines and seven surgical procedures, after which amputation of the right foot was suggested. At this stage the patient chose to consult a homeopathic physician. Through individualized homeopathic therapy, the abscess was cured within seven months and the patient was able to walk independently without pain. Whilst the patient was deprived of conventional therapy, namely amputation, homeopathic treatment enabled the patient to retain her limb and regain her mobility.